The Significance of Thiol/Disulfide Homeostasis and Ischemia-modified Albumin Levels in Assessing Oxidative Stress in Obese Children and Adolescents - Eda Mengen; Seyit Ahmet Uçaktürk; Pınar Kocaay; Özlem Kaymaz; Salim Neşelioğlu; Özcan Erel (Galenos Yayincilik, 2020)
Objective:There is an association between obesity and several inflammatory and oxidative markers in children. In this study, we analyzed thiol/disulfide homeostasis and serum ischemia-modified albumin (IMA) levels for the first time in order to clarify and determine the oxidant/antioxidant balance in metabolically healthy and unhealthy children.Methods:This study included obese children and healthy volunteers between 4-18 years of age. The obese patients were divided into two groups: metabolically healthy obese (MHO) and metabolically unhealthy obese (MUO). Biochemical parameters including thiol/disulfide homeostasis, and IMA concentrations were analyzed.Results:There were 301 recruits of whom 168 (55.8%) were females. The obese children numbered 196 (MHO n=58 and MUO n=138) and healthy controls numbered 105. No statistically significant difference could be found in ages and genders of the patients among all groups (p>0.05, for all). Native thiol (SH), total thiol (SH+SS), and native thiol/total thiol (SH/SH+SS) ratio were statistically significantly lower in the MUO group than the control group (p<0.001, p=0.005, and p=0.005; respectively). Disulfide (SS), disulfide/native thiol (SS/SH), disulfide/total thiol (SS/SH+SS) and IMA levels were statistically significantly higher in the MUO group than the control group (p=0.002, p<0.001, p<0.001, and p=0.001, respectively).Conclusion:Chronic inflammation due to oxidative stress induced by impaired metabolic parameters in MUO children caused impairment in thiol redox homeostasis. Our data suggested that the degree of oxidant imbalance in obese children worsened as obesity and metabolic abnormalities increased. It is hypothesized that thiol/disulfide homeostasis and high serum IMA levels may be reliable indicators of oxidant-antioxidant status in MUO children.